The importance of cardiorespiratory physiotherapy in an intensive care unit: a review study (Research, Society and Development, 2023)
Introduction: Cardiorespiratory physiotherapy is currently an effective intervention in patients in intensive care units, aiming at the rehabilitation process and restoration of functional performance. Objective: to point out the benefits of cardiorespiratory physiotherapy in the rehabilitation of patients in the Intensive Care Unit, according to the evidence in the scientific literature. Methodology: an integrative review was carried out of scientific materials published in indexed journals between the years 2014 to 2022, with reference to the databases: Physical Therapy Evidence Database (PEDro), PubMed, and Scientific Electronic Library Online (SciELO), emphasizing what is most current on the subject of this discussion. Conclusion: It was found that the role of the physiotherapist in the ICU with patients with cardiorespiratory impairments is essential to promote cardiovascular health.